Development of Graphene Oxide-Based Colorimetric Sensors with Catalytic Activity for Hg2+ and Ag+ Ions Detection - Yanping, Qu (Universiti Malaysia Sarawak, 2025)
ABSTRACT This study aims to construct a novel fast-response and high-sensitivity heavy metal colorimetric sensor based on graphene oxide/nanocomposites with catalytic properties. Eventually, a paper-based colorimetric sensor is developed for rapid on-site detection of heavy metals by using test paper as a solid-phase carrier. By varying the preparation conditions (concentration, temperature, pH and time) for the composites, a simple, unlabelled colorimetric sensing method is proposed to achieve the quantitative detection of Ag+. Under optimal conditions, the detection range of Ag+ by this colorimetric sensing method is 0.5–1000 μM, and the detection limit is 0.5 μM, which is lower than the previously reported detection limit of the unlabelled Ag+ colorimetric sensing method, indicating increased sensitivity and detection range. Furthermore, incorporating Au into the composite with varying the Au-to-Pt ratio, GO concentration, temperature, time and pH allowed the achievement of a simple and rapid on-site simultaneous detection of Ag+ and Hg2+. Under the optimal detection conditions, the colorimetric sensor had a detection range of 1–10000 nM for Hg2+, with a detection limit of 1 nM. For Ag+, the detection range was 50–100000 nM, with a detection limit of 50 nM. Finally, by depositing a graphene oxide/platinum composite on a paper substrate, we developed a simple, fast, low-cost, naked-eye quantitative, paper-based colorimetric sensor for the simultaneous detection of Hg2+ and Ag+. The sensor has detection limits of 0.05 and 2.5 μM for Ag+ and Hg2+, respectively, and detection ranges of 0.05-10 and 2.5-100 μM, respectively. This approach provides not only a basis for on-site screening of heavy metals but also new ideas for the design of portable sensors and cross-applications in other disciplines.